A first‐in‐human, randomized, double‐blind, single‐ and multiple‐dose, phase I study of recombinant human thymosin β4 in healthy Chinese volunteers. Issue 17 (4th August 2021) - Wang, Xinghe; Liu, Long; Qi, Lu; Lei, Chunpu; Li, Pu; Wang, Yu; Liu, Chen; Bai, Haihong; Han, Chengquan; Sun, Yinjian; Liu, Jincan
Abstract: The study evaluated the safety, tolerability, pharmacokinetics (PK) and anti‐drug antibody (ADA) of the recombinant human thymosin β4 (NL005) for single and multiple intravenous injections in healthy subjects. Seven cohorts, with 54 healthy subjects, were given a single intravenous dose of NL005 or placebo and were observed for 28 days. The cohorts received ascending doses of either 0.05, 0.25, 0.5, 2.0, 5.0, 12.5 or 25.0 μg/kg in the single‐dose trial. A total of 30 healthy subjects were randomly enrolled in the multiple‐dose trial, and 3 cohorts (0.5, 2.0 and 5.0 μg/kg) were administered once human thymosin β4 daily for 10 days and observed for 28 days. The adverse events were mild to moderate in intensity. There were no dose‐limiting toxicities or serious adverse events. The plasma concentration, maximum peak concentration ( C max ) and AUC of each dose group increased with the increase in the dose. The tendency of terminal clearance in each dose group was consistent, and there was no obvious accumulation after continuous administration. Thus, the drug can be concluded to be well tolerated and safe in healthy people and suitable for use in a clinical study for the treatment of acute myocardial infarction.